THE CURRICULUM: PERSPECTIVES FOR ITS INTERPRETATION - Malagón Plata, Luis Alberto (Investigación y Educación en Enfermería, 2009)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> This article reflects on the concepts of curriculum, and considers its object of study, and the tendencies, currents or curricular perspectives that are more re-presentative. The idea of beginning the article with the search for a definition of curriculum and a delimitation of its object, points to clarify the discussion about the variables involved in the concept. The second section entails the discussion about currents or curricular perspectives, with the purpose of delimiting the reaches of each one in relation with the variable of pertinence. To portray, from the point of view of each one, which could favor the processes of social and integral pertinence. The expositions and experiences in respect to it, allows us to argument our cause.